(untitled) (AACINI - International Journal of Industrial Engineering, 2024)
Organizational networks constitute an original and promising phenomenon in today’s societies since they represent new ways of exchanging information, articulating solidarity efforts and facilitating learning processes between different organizations and social actors. This paper addresses this issue within the framework of an investigation that analyzes the case of the CARICET Network, "Advisory Committee of Interregional Representatives of Certification of Technical Specialties" of the Certification Program of technical specialties or trades of the National Technological University in the period 2009 -2019 within the industrial sector, within the framework of a multisectoral articulation. To approach the term network, the theoretical line of the network society and the new informational paradigm as a new way of understanding the functioning of society based on globalization, an event that has been developing thanks to the Internet, is of particular interest. In this sense, it is proposed to determine the way in which the social dialogue of multisectoral actors manages to articulate and implement a certification system for technical specialties, where each node (Regional College) of the network meets, satisfies the territorial needs and of the different actors highlighting the workers and their productive knowledge without which said device would not exist. The configuration of the institutional framework for the construction of said CARICET Network as a zone of innovation and shared learning is a very enriching capital for the National Technological University, which can be transferred to other initiatives